Analisis Pengendalian Persediaan Kemasan untuk Minyak Goreng pada CV.XYZ - Ulfah, Siti Maria; Eka Dewi Karunia Wati, Putu (Fakultas Teknik UMRI, 2024)
In this study, analysing the stockpiles of raw material in CV.XYZ packaging that suffered from excessive stocks causing damage to the packaging, there were four types of packaging: 400 ml, 900 ml, 1000 ml, and 5000 ml.This research took about four months. Then he will know that the request in the past will be estimated by means of an average estimate. He did a calculation against the losses suffered by the company and then the rebooking point of the packaging. Based on the results of this research, the re-ordering point is on a 400 ml pack of 7566 pcs, a 900ml pack of 13575 pcs, a 1000 ml package of 17658 pcs and a 5000 ml packing of 8472 pcs. But it would be better for the company to repurchase one day when the packaging is left for only one production process.